Genetic ablation of cyp8b1 preserves host metabolic function by repressing steatohepatitis and altering gut microbiota composition - Patankar, Jay; Wong, Chi K.; Morampudi, Vijay; Gibson, William T.; Vallance, Bruce; Ioannou, George N.; Hayden, Michael R. (American Journal of Physiology-Endocrinology and Metabolism, 2018)
Genetic ablation of Cyp8b1 preserves host metabolic function by repressing steatohepatitis and altering gut microbiota composition. Am J Physiol Endocrinol Metab 314: E418–E432, 2018. First published October 24, 2017; doi:10.1152/ajpendo. 00172.2017.—Both type 2 diabetes (T2D) and nonalcoholic steatohepatitis (NASH) are associated with reduced hepatic mitochondrial respiratory capacity. Cholic acid (CA) is the predominant 12α-hy-droxylated bile acid that regulates hepatic lipid metabolism, and its circulating levels are negatively correlated with insulin resistance. Abolishing CA synthesis via the genetic disruption of the enzyme sterol 12α-hydroxylase (Cyp8b1-/-) leads in resistance to diabetes and hepatic steatosis. Here, we show that long-term stimulation of hepatic lipogenesis leads to a severe impairment in overall metabolic and respiratory function in control mice (Cyp8b1+/+) but strikingly not in Cyp8b1-/- mice. Cyp8b1-/- mice are protected from such metabolic impairments associated with T2D and NASH by inhibiting hepatic de novo lipogenic gene and protein expression and altering gut microbiota composition. The protective phenotype is compromised when NASH induction is independent of impairment in de novo lipogenesis (DNL). Consequently, Cyp8b1-/- mice also show a reduction in hepatic inflammation and fibrosis along with a shift in antimicrobial dynamics in the small intestine. Our data show that the altered bile acid composition of Cyp8b1-/- mice preserves metabolic and respiratory function by repressing hepatic DNL and driving favorable changes in gut antimicrobial responses.
Created from Fastlane, Scopus look-up
Keywords: 12α-hydroxylated bile acids; Cyp8b1; FXR; Gut microbiota; Nonalcoholic hepatic steatosis